STRATEGI KOMUNIKASI DINAS KEBUDAYAAN KOTA MEDAN DALAM MELESTARIKAN TARIAN SERAMPANG DUA BELAS DI KOTA MEDAN - Indah Sofia Maria Sipayung; Emmelia A. Ginting; Irene Silviani (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study aims at determining the communication strategy used by the Department of Culture in an effort to preserve the Serampang Dua Belas Dance in Medan City and the obstacles experienced in implementing communication strategies in preserving this dance. The research subjects are Policy Stakeholders at the Culture Service, Malay Community Leaders, and the owners of the Serampang Dua Belas Dance Studio in Medan City. Data collection techniques are through research in the field using observation methods and in-depth interviews with research informants and using literature or documents that support research. Data processing used is a qualitative descriptive approach. The results of the descriptive analysis of the study indicate that the communication strategy used by the Department of Culture is not as effective as before, especially in the areas of message preparation, method use, and media use. The Department's program experienced obstacles and did not run as it should, this was because the presenced of Covid-19 made the work program of the Office constrained due to budget constraints for funding the preservation program, reduction of activities, especially dance dance training, and no competitions were held in connection with the prohibition of crowds on the grounds of health protocols, and others. Preservation methods such as the Redundancy method and the Persuasive Method in the form of approached and establishing cooperative relationships with related parties such as the executive, private parties, the press, and others had not been carried out, to strive for the Serampang Dua Belas Dance to be more existent in the eyes of the public and tourists in particular.